Systolic Blood Pressure, Cardiac Index and Eisenmenger Syndrome are Predictors of Mortality in Pulmonary Arterial Hypertension-associated with Congenital Heart Disease: An Analysis from the COHARD-PH registry - Muflihatul Baroroh Rochmat; Budi Yuli Setianto; Dyah Wulan Anggrahini; Lucia Kris Dinarti; Anggoro Budi Hartopo (Majalah Kardiologi Indonesia)
Background: Pulmonary arterial hypertension (PAH) is a complication of left-to-right intracardiac shunt congenital heart disease (LtR-shunt CHD). There are several known predictors of mortality in PAH patients, however predictors of mortality in LtR-shunt CHD-associated PAH need to be validated.